Pengaruh Personality Traits Terhadap Business Sustainability dengan Competitive Advantage Sebagai Variabel Mediasi dalam Perspektif Manajemen Bisnis Syariah: Studi pada Konsumen Bakso Syukron di Bandar Lampung - Muhammad Faqih Hidayat; Suhendar Suhendar; Zathu Restie Utamie (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Personality Traits is to examine the consistency of a person's stability, namely the extroversion trait of being able to socialize in circumstances and various situations as time goes by. A person's personality or different personalities that consumers have is what causes not every time a business to experience the crowd that every entrepreneur wants. Uniqueness in a business is a characteristic that must be possessed, this characteristic is what can distinguish one business from another business. The population in this study is Syukron meatball consumers in Bandar Lampung. The number of samples used is 100 respondents. This research method is quantitative with online questionnaire data collection technique through google form with analysis method using Structural Equation model approach with SmartPLS 4 application. The data analysis technique used is mediation regression analysis (Mediation Regression Analysis). The results of this data show that Personality Traits have a positive and significant effect on Business Sustainability. Personality Traits have a positive and significant effect on Competitive Advantage, Competitive Advantage has a positive and significant effect on Business Sustainability. And Personality Traits affect Business Sustainability mediated by Competitive Advantage.